2021
DOI: 10.2147/jir.s329611
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of Novel Pancreas Cancer Prognostic Index in Unresectable Locally Advanced Pancreas Cancers Treated with Definitive Concurrent Chemoradiotherapy

Abstract: Purpose: We evaluated the prognostic quality of the novel pancreas cancer prognostic index (PCPI), a combination of CA 19-9 and systemic inflammation response index (SIRI), on the outcomes of locally advanced pancreas adenocarcinoma (LAPAC) patients who received concurrent chemoradiotherapy (C-CRT). Methods: This retrospective analysis covered 152 unresectable LAPAC patients treated from 2007 to 2019. Receiver operating characteristic (ROC) curve analysis was used to define ideal cutoff thresholds for the pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…As a result, they concluded that PS, response rate, and decreased CA 19-9 serum levels were significant prognostic factors. 39,40 Other studies have found a significantly improved survival in patients with advanced pancreatic tumor who have lower serum CA 19-9 levels, consistent with these findings. 41,42 In contrast, in another study, the tissue over-expression of CA 19-9 in DLBCL NOS was not associated with therapy response or patient survival.…”
Section: Discussionsupporting
confidence: 65%
“…As a result, they concluded that PS, response rate, and decreased CA 19-9 serum levels were significant prognostic factors. 39,40 Other studies have found a significantly improved survival in patients with advanced pancreatic tumor who have lower serum CA 19-9 levels, consistent with these findings. 41,42 In contrast, in another study, the tissue over-expression of CA 19-9 in DLBCL NOS was not associated with therapy response or patient survival.…”
Section: Discussionsupporting
confidence: 65%
“…It was shown that OS and PFS were shorter in PDAC patients with Ca19-9 ≥90 IU/mL than in a group with a Ca19-9 value of <90 IU/mL (PFS: 4.4 vs. 17.0 months, respectively, p < 0.001; OS 7.4 vs. 26.1 months, respectively, p < 0.001). The results confirmed a significant association between elevated Ca19-9 levels and reduced survival results in PDAC patients [46].…”
Section: Ca19-9supporting
confidence: 72%
“…43 The results of such studies have essentially always confirmed the significant prognostic usefulness of such biological indicators, regardless of the chosen treatment approach. [14][15][16][17][18][19][20][21][22][23][24][25][26] The PIV, a newly discovered relevant indicator of…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, growing evidence suggested that chronic systemic inflammation was a key factor underlying the variations in PAC prognoses following similar treatment regimens, regardless of whether the tested index was a single marker or a specific combination. [14][15][16][17][18][19][20][21][22][23][24][25][26] The pan-immune-inflammation index (PIV), a unique blend of circulating platelets, monocytes, neutrophils, and lymphocytes, is another recently developed biomarker. Previous research has found strong links between pretreatment levels of PIV and clinical outcomes in cancers such as colorectal, breast, esophageal, and small-cell lung cancers, Merkel cell carcinomas, and malignant melanomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation